Autocorrelation Reflectivity of Mars. Issue 16 (10th August 2020) - Deng, Sizhuang; Levander, Alan
Abstract: The seismic structure of the Martian interior can shed light on the formation and dynamic evolution of the planet and our solar system. The deployment of the seismograph carried by the InSight mission provides a means to study Martian internal structure. We used ambient noise autocorrelation to analyze the available vertical component seismic data to recover the reflectivity beneath the Insight lander. We identify the noise that is approximately periodic with the Martian sol as daily lander operations and the diurnal variation in Martian weather and tides. To investigate the seismic discontinuities at different depths, the autocorrelograms are filtered and stacked into different frequency bands. We observe prominent reflection signals probably corresponding to the Martian Moho, the olivine‐wadsleyite transition in the mantle, and the core‐mantle boundary in the stacked autocorrelograms. We estimate the depths of these boundaries as ~35, 1, 110–1, 170, and 1, 520–1, 600 km, consistent with other estimates. Plain Language Summary: Knowledge of the Martian interior informs theories for the formation and dynamic evolution of another terrestrial planet, hence providing information on the history of the solar system. On Earth, subsurface structure is discovered by analysis of seismic signals recorded by large seismograph arrays deployed worldwide. The InSight lander carried one seismic station to Mars at the end of 2018, providing the opportunity to investigate the internal structure of Mars. Here we autocorrelated ambient noise from the available seismic data to investigate the subsurface discontinuities of Mars. In the raw seismic data, we observe the long‐period signals with a period of ~1 Martian sol (~3% longer than an Earth day), which are related to the diurnal variation in weather and tides. After the removal of instrument response, remaining high‐amplitude peaks are likely caused by the daily operations of the InSight lander. We preprocessed the raw data and used different frequency bands to detect discontinuities at different depths. We identify prominent signals in the stacked autocorrelation reflectivity as likely originating from the Martian Moho, the olivine‐wadsleyite transition in the Martian mantle, and the core‐mantle boundary. These results are consistent with other observations and measurements. Key Points: Autocorrelation analysis of SEIS data shows signals probably from the Martian Moho, olivine‐wadsleyite transition, and core‐mantle boundary Depth conversion of these signals gives discontinuity depths consistent with estimates made with other methods A high crustal Vp/Vs ratio suggests the composition of Martian crust is composed of basaltic and andesitic rocks